تطوير نموذج تجريدي لتوصيف خصائص الشبكات المتغيرة - دندة رضوان; قبلان قاسم; يوسف سوسن (Latakia University Journal -Engineering Sciences Series, 2017)
نظراً للعدد الكبير من قواعد النفاذ المعرفة للشبكات والتغير الديناميكي لطوبولوجيا الشبكات, فإن التحقق اليدوي من الخواص المهمة في الشبكة مثل الوصولية, عدم تضارب القواعد وعدم وجود حلقات أمراً صعباً على المبرمج. يعدَ التوصيف الصوري(Formal Specification) للأنظمة والبروتوكولات من أهم الطرق التي تستخدم لإزالة الغموض في تعريفات الأنظمة واكتشاف الثغرات في عملها. هناك العديد من الأبحاث التي قدمت في مجال توصيف وصولية الرزم في الشبكات لكن القليل منها تم اختبارها عبر أدوات فحص النماذج التي تساعد في كشف أخطاء هذه النماذج. في هذا البحث تم تطوير نموذج تجريدي من أجل توصيف الشبكات الديناميكية ليصبح مناسباً للتحقق من مجموعة من الخصائص المهمة ومنها وصولية الرزم, عدم وجود التضاربات..الخ اعتماداً على ترميز حالة الشبكة. تم تحقيق النموذج المقترح الذي يوصف الشبكة بواسطة لغة المنطق المؤقت للأفعال(Temporal Logic of Action) ,TLA+ والتي هي عبارة عن لغة توصيف عالية المستوى, تعتمد على نظرية المجموعات والجبر المنطقي الأولي. تم تحليل النموذج وفحص خصائصه باستخدام أداة فحص النماذج TLCالمستخدمة مع الأداة TLA, تظهر النتائج صحة النموذج وتحسيناً من ناحية تخفيض زمن استجابة وعدد الحالات المطلوبة للحصول على نتيجة التحقق. According to the large number of the access rules that define the networks, and the dynamic changing of the network topology, that is the verification by hand of the important properties in the network such as reachability, access rules conflict free and loop free is so hard to accomplish by the programmer. Formal specification of systems and protocols is considered one of the most important methods that is used to eliminate the ambiguous of the system configurations and find bugs of its work. A lot of the researches have been introduced in packet reachability and network specification domain, but a little of them are checked and analyzed by model checkers which help to detect the errors of these models. In this paper an abstraction model for dynamic networks specification has been introduced and developed to be appropriate for several important properties of the network such as reachability, no conflict..etc, depending on the network state. The proposed model specification is implemented by TLA+(Temporal Logic of Action) language which is a high level specification language built on Set-theory and First Order Logic, the model has been analyzed and the properties are checked by TLC model checking tool which used by TLA tool. Results show the correctness of the model, and improvement in reducing the response time and the required states to get the result of the verification.